2004
DOI: 10.1038/sj.bmt.1704426
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, outcome, and risk factors of late-onset noninfectious pulmonary complications after unrelated donor stem cell transplantation

Abstract: Summary:We evaluated the incidence, the risk factors, and the outcome of late-onset noninfectious pulmonary complications (LONIPCs) among 50 patients who underwent allogeneic stem cell transplantation from unrelated donors. Of the 39 patients surviving at least 3 months, 10 (26%) fulfilled the diagnostic criteria of LONIPCs and were further subclassified as having bronchiolitis obliterans (four patients), bronchiolitis obliterans with organizing pneumonia (four patients), and interstitial pneumonia (two patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
93
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 27 publications
10
93
1
1
Order By: Relevance
“…Sakaida et al 3 described the association between late-onset, non-infectious pulmonary complications, including BOS with chronic extensive GVHD and lower relapse incidence but not with overall survival. Several studies 10,11,24 showed the negative impact of BOS on outcome variables. We hypothesize that frequently routine PFTs may improve clinical outcome detecting less severe BOS, which may respond to immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sakaida et al 3 described the association between late-onset, non-infectious pulmonary complications, including BOS with chronic extensive GVHD and lower relapse incidence but not with overall survival. Several studies 10,11,24 showed the negative impact of BOS on outcome variables. We hypothesize that frequently routine PFTs may improve clinical outcome detecting less severe BOS, which may respond to immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…9 The incidence of BOS in several other publications ranged from 8.3% to 26%. 3,5,10,11 These differences may be attributed to differences in the definition of BOS, conditioning protocol's toxicity, GVHD prophylaxis, hematopoietic stem cell source and HLA compatibility. In this regard, recent data have shown that non-myeloablative conditioning protocols correlate with a decline in the incidence of bronchiolitis obliterans after allo-HCT.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we cannot evaluate the usefulness of pretransplant PFTs. Although abnormal post-transplant PFTs are also reported to predict LONIPCs, 38 only four patients had abnormal PFTs between allo-HSCT and onset of BO in our cohort. These results indicate that it is difficult to detect airway obstruction before the appearance of respiratory symptoms unless PFTs are more frequent.…”
Section: Discussionmentioning
confidence: 81%
“…Almost all of the previous studies were limited to case reports or series that did not include more than 10 cases of COP/BOOP, and/ or did not analyze COP/BOOP independently but rather as a part of late-onset non-infectious pulmonary complications. 6,7,[10][11][12][14][15][16][17] To the best of our knowledge, only one report, from Seattle, has included more than 20 cases (49 cases with COP/BOOP). 8 Thus, we performed a large retrospective study that included about 200 patients with COP/BOOP.…”
Section: Introductionmentioning
confidence: 99%